Insights into ecological and reproductive aspects of two cryptogenic peracarid crustaceans of the Argentinian coast - Fricke, Anna (2015)
Peracarid crustaceans belong to the most important agglomerating macrofauna in sedimentary habitats. The amphipod Monocorophium insidiosum CRAWFORD, 1937 and the tanaid Tanais dulongii AUDOUIN, 1926 are listed as invasive species. In the present study, we investigated the ecology of M. insidiosum and T. aff. dulongii from the Argentinian coast. Both crustaceans were breeding under laboratory conditions to study their fecundity and growth. Additionally their behavior and potential interspecific relations have been investigated in four different laboratory experiments. We evaluated tube building capabilities (experiment 1), and tested gender specific responses of M. insdiosum to the presence of empty (experiments 2 and 3), and inhabited T. aff. dulongii tubes (experiment 4). Our results showed high fecundity (three generations within four weeks) and growth rates (duplication of body lengths in two weeks) for M. insidiosum. Two tube construction strategies were distinguished: a tube changing behavior for the amphipod M. insidiosum, showing greater construction activity for females, and tube keeping behavior for T. aff. dulongii. Overall, tanaid tubes were frequently claimed by M. insidiosum, demonstrating a close interspecific relationship and resulting in decreased sediment aggregating activity. In the light of our observations it may be affirmed that these invasive species are probably frequently distributed along the Patagonian Atlantic coast and will still spread in future.